Occurrence of Quesada gigas on Schizolobium amazonicum trees in Maranhão and Pará States, Brazil - Zanuncio, José Cola; Pereira, Fabrício Fagundes; Zanuncio, Teresinha Vinha; Martinelli, Nilza Maria; Pinon, Tobias Baruc Moreira; Guimarães, Edylene Marota (Pesquisa Agropecuaria Brasileira, 2004)
An infestation of Quesada gigas Olivier (Hemiptera: Cicadidae) on “paricá” Schizolobium amazonicum (Huber) Ducken (Fabales: Fabaceae) was reported in the Municipalities of Itinga, Maranhão State and Paragominas, Pará State. Nymphs of this insect on roots and adults and exuvias on trunks of the plant were observed. Exit holes of nymphs in the soil were also observed. The occurrence of Q. gigas on S. amazonicum shows the damage potential of this species and the necessity of developing integrated management programs for species of this group, specially in reforested areas with “paricá”.
Keywords: Cicadidae; cicada; reforestation; soil pest; paricá